Benzyl Phenylsemicarbazides: A Chemistry-Driven Approach Leading to G Protein-Biased Dopamine D4 Receptor Agonists with High Subtype Selectivity - Pirzer, Anna; Lasch, Roman; Friedrich, Heike; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Journal of Medicinal Chemistry, 2019)
Many subtype-selective dopamine receptor ligands developed for the D2-D4 family incorporate a 1-arylpiperazine-derived primary recognition motif, which is connected to a lipophilic moiety occupying an extended binding pocket (EBP) of the receptor via an aliphatic linker of variable lengths. The evaluation of a novel group of dopamine receptor ligands now showed that highly subtype-selective ligands [up to Ki(D4.4) = 0.25 nM, D2L/D4.4 = 320, D3/D4.4 = 710 for APH199 (17)] can be obtained by choosing a relatively large and conformationally flexible 1-benzyl-1-phenylsemicarbazide substructure to fill the EBP. The novel chemotype APH199 (17) was found to act as a full agonist at the D4 receptor showing significant bias toward G protein activation over β-arrestin recruitment in comparison to quinpirole.
CRIS-Team Scopus Importer:2019-11-15

Bivalent ligands promote endosomal trafficking of the dopamine D3 receptor-neurotensin receptor 1 heterodimer - Budzinski, Julian; Maschauer, Simone; Kobayashi, Hiroyuki; Couvineau, Pierre; Vogt, Hannah; Gmeiner, Peter; Roggenhofer, Anna; Prante, Olaf; Bouvier, Michel; Weikert, Dorothée (Communications Biology, 2021)
Bivalent ligands are composed of two pharmacophores connected by a spacer of variable size. These ligands are able to simultaneously recognize two binding sites, for example in a G protein-coupled receptor heterodimer, resulting in enhanced binding affinity. Taking advantage of previously described heterobivalent dopamine-neurotensin receptor ligands, we demonstrate specific interactions between dopamine D3 (D3R) and neurotensin receptor 1 (NTSR1), two receptors with expression in overlapping brain areas that are associated with neuropsychiatric diseases and addiction. Bivalent ligand binding to D3R-NTSR1 dimers results in picomolar binding affinity and high selectivity compared to the binding to monomeric receptors. Specificity of the ligands for the D3R-NTSR1 receptor pair over D2R-NTSR1 dimers can be achieved by a careful choice of the linker length. Bivalent ligands enhance and stabilize the receptor-receptor interaction leading to NTSR1-controlled internalization of D3R into endosomes via recruitment of β-arrestin, highlighting a potential mechanism for dimer-specific receptor trafficking and signalling.
CRIS-Team Scopus Importer:2021-09-24

Detection of Elevated Risk for Drug-Related Problems in the Hospital - Jung-Poppe, Lea; Pfistermeister, Barbara; Nicolaus, Hagen; Roggenhofer, Anna; Altenbuchner, Anna; Andrikyan, Wahram; Ströbel, Armin; Schnitzer, Christine; Dormann, Harald; Maas, Renke (Deutsches Ärzteblatt international, 2024)
CRIS-Team Scopus Importer:2025-02-03

Radical Carbofluorination of Alkenes with Arylhydrazines and Selectfluor: Additives, Mechanistic Pathways, and Polar Effects - Pirzer, Anna; Alvarez, Eva-Maria; Friedrich, Heike; Heinrich, Markus (Chemistry - A European Journal, 2019)
Radical carbofluorination reactions starting from arylhydrazines and nonactivated alkenes, in which the C-F bond is formed through the use of Selectfluor, can be improved through the addition of anisole. Because direct trapping products could be detected only in trace amounts, anisole does primarily act as a reversible scavenger for the highly reactive ammonium radical dication released from Selectfluor in the C-F bond-forming step. As shown for three diverse substitution patterns, the main role of anisole is to prevent, or at least reduce, the undesired addition of the ammonium radical dication to the alkene, which in turn leads to an unfavorable consumption of the arylhydrazine-derived precursors required for carbofluorination. Moreover, besides the remarkable polar effects in radical trapping, this study shows that the Selectfluor-derived nitrogen-centered radical dication may add directly to alkenes, which has not been described so far.
CRIS-Team WoS Importer:2019-03-06

Selective Functionalization of Graphene at Defect-Activated Sites by Arylazocarboxylic tert-Butyl Esters - Halbig, Christian E.; Lasch, Roman; Krüll, Jasmin; Pirzer, Anna; Wang, Zhenping; Kirchhof, Jan N.; Bolotin, Kirill I.; Heinrich, Markus; Eigler, Siegfried (Angewandte Chemie International Edition, 2019)
The development of versatile functionalization concepts for graphene is currently in the focus of research. Upon oxo-functionalization of graphite, the full surface of graphene becomes accessible for C-C bond formation to introduce out-of-plane functionality. Herein, we present the arylation of graphene with arylazocarboxylic tert-butyl esters, which generates aryl radicals after activation with an acid. Surprisingly, the degree of functionalization is related to the concentration of lattice vacancy defects in the graphene material. Consequently, graphene materials that are free from lattice defects are not reactive. The reaction can be applied to graphene dispersed in solvents and leads to bitopic functionalization as well as monotopic functionalization when the graphene is deposited on surfaces. As the arylazocarboxylic tert-butyl ester moiety can be attached to various molecules, the presented method paves the way to functional graphene derivatives, with the density of defects determining the degree of functionalization.
CRIS-Team WoS Importer:2019-03-20

Systematic Review of Risk Factors Assessed in Predictive Scoring Tools for Drug-Related Problems in Inpatients - Jung-Poppe, Lea; Nicolaus, Hagen; Roggenhofer, Anna; Altenbuchner, Anna Maria; Dormann, Harald; Pfistermeister, Barbara; Maas, Renke (Journal of Clinical Medicine, 2022)
Drug-related problems (DRP, defined as adverse drug events/reactions and medication errors) are a common threat for patient safety. With the aim to aid improved allocation of specialist resources and to improve detection and prevention of DRP, numerous predictive scoring tools have been proposed. The external validation and evidence for the transferability of these tools still faces limitations. However, the proposed scoring tools include partly overlapping sets of similar factors, which may allow a new approach to estimate the external usability and validity of individual risk factors. Therefore, we conducted this systematic review and analysis. We identified 14 key studies that assessed 844 candidate risk factors for inclusion into predictive scoring tools. After consolidation to account for overlapping terminology and variable definitions, we assessed each risk factor in the number of studies it was assessed, and, if it was found to be a significant predictor of DRP, whether it was included in a final scoring tool. The latter included intake of >= 8 drugs, drugs of the Anatomical Therapeutic Chemical (ATC) class N, >= 1 comorbidity, an estimated glomerular filtration rate (eGFR) <30 mL/min and age >= 60 years. The methodological approach and the individual risk factors presented in this review may provide a new starting point for improved risk assessment.
CRIS-Team WoS Importer:2022-09-16

Ullmanns Encyclopedia of Industrial Chemistry: Antiparasitics (P) - Pirzer, Anna; Fürst, Michael; Heinrich, Markus (Ullmanns Encyclopedia of Industrial Chemistry, 2018)